FACTORS ASSOCIATED WITH SUBJECTIVE COMPLAINTS OF LOW BACK PAIN IN TAILORS AT THE CHILDREN'S PALACE MARKET, JAMBI CITY - Putri Sahara Harahap; Fhala Sasqia Ashar; Sugiarto Sugiarto (Bajang Institute, 2023)
Sewing is one of the risky jobs to experience low back pain (LBP) this is due to working with long sitting and non-ergonomic work positions. The Jambi City Children's Palace Market is the central tailor in Jambi City. The results of the observation showed that from 10 tailors, 7 experienced pain in the lower back when sewing. The purpose of the study was to determine the factors associated with complaints of LBP on tailors at the Children's Palace Market. The study used a cross sectional design. The research was conducted at the Istana Children's Market in Jambi City on 10-31 May 2022. The research population was all tailors at the Istana Anak Market. The research sample was 30 tailors at the Children's Palace Market in Jambi City. The research instrument was a questionnaire and RULA. Data collection techniques using interviews and observations of respondents' work attitudes. Data were analyzed using chi square test. As many as 53.3% of respondents have complaints of low back pain, 53.3% of respondents work with high-risk work attitudes, 60.0% of respondents work with risky work durations and 63.3% of respondents have long tenures. The results of the bivariate analysis showed that there was a relationship between work attitude (p=0.000) and tenure (p=0.011) with complaints of low back pain in tailors at the Children's Palace Market, Jambi City. There is no relationship between work duration (p-0.159) and complaints of low back pain in tailors at the Children's Palace Market, Jambi City.